Urban politics, conspiracy and reform in Nampula, Mozambique - Sumich, Jason (2009)
This paper presents an anthropological analysis of urban politics in post-reform Mozambique. The author canvassed local opinion on an organ-trafficking scandal which took place in Nampula city in 2003. He challenges the anthropological argument that high levels of belief in the occult signify a 'people's critique' of neo-liberalism, suggesting instead that this argument more accurately reflects the fears of the rich than the poor. Rather than dismantling the existing political structures that major international donors and institutions have viewed as 'pathological', neo-liberal reforms in Mozambique have revitalised the power of the party state and increased dependence of certain groups on the ruling party. External actors must recognise that outside resources intended to reward neo-liberal reforms may not reflect gains in 'good governance' and 'transparency', but rather reinforce the status and influence of the regime. This research underscores the fact that neo-liberal reforms cannot be viewed as a unified set of changes and can often produce problematic and unintended consequences. Further attention must be paid to the historical continuity of events that accompany wider processes of neo-liberal reform.